Trametes polyzona, an emerging filamentous basidiomycete in Réunion Island. Issue 6 (16th February 2017) - Gauthier, Alexandre; Jaubert, Julien; Traversier, Nicolas; Lemant, Jérôme; Balu, Laurent; Garcia‐Hermoso, Dea; Welti, Stephane; Favel, Anne; Picot, Sandrine; Hoarau, Gautier
Summary: We describe two serious Trametes polyzona pulmonary infections, which occurred in Réunion Island, in critically ill patients. The identification was performed using sequencing of the internal transcribed spacer region of ribosomal DNA and D1/D2 region of 28S rDNA. In one case, the significance of T. polyzona in the pathological process was certain, proven by histopathological evidence of fungal lung infection. T. polyzona, an emerging filamentous basidiomycete, prevalent in tropical areas, has not been described so far in human infections.